Tanggung Jawab Pelaku Usaha Atas Kualitas Produk Dan Kepuasan Konsumen: Studi Kasus Miss Daster Indonesia - Revi Mariska; Ucuk Agiyanto; Ferry Irawan Febriansyah (Fakultas Hukum Universitas Riau, 2026)
This quantitative study aims to analyze the influence of business actors’ responsibility on product quality and consumer satisfaction, with Miss Daster Indonesia as the research focus. In the digital commerce era, the increasing number of marketplace transactions requires business actors to ensure product quality, accurate information disclosure, and consumer rights protection. This research employs a quantitative survey approach involving respondents who have previously purchased Miss Daster Indonesia products through online marketplaces. A Likert-scale questionnaire was used to measure variables such as product information accuracy, product quality, after-sales service effectiveness, and consumer satisfaction levels. The collected data were analyzed using descriptive statistics and regression tests to determine the influence of independent variables on consumer satisfaction. The findings show that business responsibility reflected in the accuracy of product descriptions, material quality, and responsiveness of after-sales service significantly affects consumer satisfaction. However, several issues, such as product discrepancies and slow complaint handling, were still identified and negatively influenced consumer perceptions. These results highlight the need for improved consistency in product quality, transparent information, and faster complaint-response mechanisms to strengthen consumer trust and satisfaction.